Hedyotis puberulifolia (Rubiaceae), a new species from Guangdong, China - Xu, Yi-Da; Wang, Rui-Jiang (Phytotaxa, 2021)
Hedyotis puberulifolia from eastern Guangdong province, China, is described and photographed here. It is clearly different from all other congeneric species by its puberulous stem, leaves, stipules, and thyrsoid inflorescence with monochaisal sub-axes. Phylogenetic analysis revealed that H. puberulifolia is closely related to the sympatric H. tenuipes. It is evaluated as Least Concern according to IUCN Red List Categories and Criteria.